DEVELOPMENT OF SKILLS AND ABILITIES OF SPEECH COMMUNICATION OF STUDENTS - Mirxanova Matlyuba Sadikovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article discusses issues related to the development of skills of speech communication. The author in a lively, accessible manner helps to systematize and deepen his knowledge on this issue. In addition, the article deals with difficulties in teaching speech communication. And also the author gives examples of different methods for teaching foreign students speech communication in Russian.